Tafsir Kontekstual Ayat-ayat Riba dalam Era Digital: Relevansi Ulama Tentang Mata Uang Kripto dan Implikasinya bagi Ekonomi Umat - Salis Azkia; Salwa Salsabila; Fahmi Abdul Mukhsi; Lina Marlina (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This research analyzes the fundamental conflict between state regulation and Sharia principles regarding cryptocurrency in Indonesia, aiming to explore the views of Islamic scholars and the legal perspective in the Qur'an and its interpretations. Cryptocurrency has become a popular investment trend, especially among the youth. While the Bank Indonesia (BI) prohibits its use as a legal payment instrument, its trading activity is legalized as an investment asset under the supervision of OJK and BI. Conversely, the MUI Fatwa and the majority of scholars declare crypto transactions as forbidden (haram) due to the presence of elements prohibited in Islamic economics: riba (usury) and gharar (uncertainty). Gharar is linked to the extreme price volatility that encourages speculation (maysir) and the non-physical nature of crypto. Riba, on the other hand, is associated with the potential for unfair profit in lending and staking mechanisms. This prohibition is rooted in the interpretation of the Qur'an (QS. Al-Baqarah: 275 and QS. An-Nisa: 29), which strictly forbids riba and consuming others' wealth through bathil (unlawful) means. Consequently, although legally accepted as an investment asset, many scholars view crypto as violating the principles of justice and transparency in Islamic economics.